Analysis of cervical and breast cancer screening behavior and its influencing factors among urban and rural women in Beijing. - Yanqing Gao; Guoxin Liang; Chun Chang; Feng Pan; Fumin Huang; Litong Gong; Liyu Huang (PLoS ONE)
Objective To clarify the screening behavior and influencing factors of females with breast cancer and cervical cancer in suburban areas and to provide a scientific basis for the subsequent implementation of targeted health education, intervention measures and the formulation of relevant policies. Methods This study used a multi-stage stratified random sampling method to select 4, 000 women in urban and rural areas of Beijing to analyze their behavior, basic situation, and influencing factors regarding cervical and breast cancer screening. Results The sample size of the final included valid analysis was 3861 people, and the screening rate was 27.25% for cervical cancer, 20.64% for breast cancer, 30.46% for at least one screening and 17.43% for both cervical cancer and breast cancer screening. The rate of four screening conditions was greater in urban areas (PCervical cancer screening = 31.1%, PBreast cancer screening = 22.0%, PAt least one = 33.9%, PBoth cancers were screened = 19.1%) than in rural areas (PCervical cancer screening = 22.6%, PBreast cancer screening = 19.0%, PAt least one = 26.2%, PBoth cancers were screened = 15.4%) and was greater with medical insurance (PCervical cancer screening = 28.7%, PBreast cancer screening = 21.7%, PAt least one = 32.0%, PBoth cancers were screened = 18.5%) than without medical insurance (PCervical cancer screening = 12.8%, PBreast cancer screening = 10.3%, PAt least one = 15.6%, PBoth cancers were screened = 7.5%). The highest percentage of the four screening conditions was found in the 45-59-year-old group (PCervical cancer screening = 36.0%, PBreast cancer screening = 29.8%, PAt least one = 39.5%, PBoth cancers were screened = 26.4%). The rate of cervical cancer screening behavior increased with increasing education level and family per capita monthly income, and the highest percentage of respondents had a college education or above (PCervical cancer screening = 35.2%, PBreast cancer screening = 23.6%, PAt least one = 38.2%, PBoth cancers were screened = 20.6%), as did the percentage of families whose per capita monthly income was above 15, 000 yuan (PCervical cancer screening = 34.7%, PBreast cancer screening = 27.3%, PAt least one = 38.3%, PBoth cancers were screened = 23.6%). Multivariate analysis revealed that an age range of 45 to 59 years (PAll four screening conditions were obtained<0.001), an education level of junior high school, a high school (PAll four screening conditions were obtained<0.001), a college education or above (PAll four screening conditions were obtained<0.001), a marital status of a spouse (PAll four screening conditions were obtained<0.001), a divorce status (PAll four screening conditions were obtained<0.001) or a widowhood status (PAll four screening conditions were obtained<0.001), and a medical insurance status (PAll four screening conditions were obtained<0.001) were positively correlated with the percentages of the four screening behaviors. Conclusion The level of "two- cancer" screening behavior of suburban residents in Beijing still warrants improvement, and precision nutrition and health communication and intervention should be carried out continuously for rural residents, individuals under age 45, unmarried individuals, individuals with a primary school education and below, and people without medical insurance.